2023
DOI: 10.1038/s41467-022-35611-9
|View full text |Cite
|
Sign up to set email alerts
|

Ex-situ generation and synthetic utilization of bare trifluoromethyl anion in flow via rapid biphasic mixing

Abstract: Fluoroform (CF3H) is the simplest reagent for nucleophilic trifluoromethylation intermediated by trifluoromethyl anion (CF3–). However, it has been well-known that CF3– should be generated in presence of a stabilizer or reaction partner (in-situ method) due to its short lifetime, which results in the fundamental limitation on its synthetic utilization. We herein report a bare CF3– can be ex-situ generated and directly used for the synthesis of diverse trifluoromethylated compounds in a devised flow dissolver f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…In 2023, Kim et al reported the reaction of 1 equivalent of CF 3 H with a Schlosser-Lochmann base generated from PhLi and KO t Bu in a flow system (Scheme 18). 26 The originally developed built-in devices for mixing the gaseous and liquid phases has been employed to improve the mixing efficiency, and 1 equivalent of CF 3 H was successfully reacted.…”
Section: Short Review Synthesismentioning
confidence: 99%
“…In 2023, Kim et al reported the reaction of 1 equivalent of CF 3 H with a Schlosser-Lochmann base generated from PhLi and KO t Bu in a flow system (Scheme 18). 26 The originally developed built-in devices for mixing the gaseous and liquid phases has been employed to improve the mixing efficiency, and 1 equivalent of CF 3 H was successfully reacted.…”
Section: Short Review Synthesismentioning
confidence: 99%
“…The microflow trifluoromethylation of carbonyls using HFC‐23 via the ex‐situ generation of the trifluoromethyl anion in a devised flow dissolver was developed by Kim et al in 2023 (Figure 32). [47] Initially, they found that using a simple tubing flow reactor or a tube‐in‐tube microfluidic reactor was inappropriate for rapid gas‐liquid biphasic mixing and controlling the CF 3 anion. Therefore, a gas‐liquid flow device (GLD) was developed for rapid biphasic mixing and handling of the unstable trifluoromethyl anion.…”
Section: Microflow Trifluoromethylationmentioning
confidence: 99%